Influence of non-productive operations on product quality - Eniko, Peter (Strojniški vestnik, 2016)
This paper addresses the study of piston bore machining. Within the framework of an experimental investigation single and combined effects and related reproducibility of such parameters on bore geometry and surface finish were investigated. Experiment planning and process modelling were performed by design of experiments (DOE) methodology. The experimental part was carried out in a regular production which is affected by non-productive operations that influence product quality. Based on the reaming process state of the art review and previous industrial experiences feed rate and spindle speed were identified as key productive operation factors in achieving bore cylindricity and surface roughness. Non-productive operations, such as clamping, washing and degreasing of the workpiece that negatively impacted results, were identified during experimental work with scanning electron microscope (SEM) analysis and pattern recognition in statistical process control (SPC) control chart. Negative impacts of non-productive operations were minimized with corrective actions. Regression analyses give models for both responses under consideration, namely bore cylindricity and surface roughness, and are at adequate confidence level. Experiments conducting, analysis and corrective actions are included in optimization strategy model which is schematically shown and interpreted in discussion.
Keywords: cilindričnost; DOE; hrapavost površine; pranje; razmaščevanje